EFFECT OF FALSE FLAX MEAL ON CERTAIN GROWTH, SERUM AND MEAT PARAMETERS OF JAPANESE QUAILS - T. Bulbul; A. Rahman; V. Ozdemir (Journal of Animal and Plant Sciences, 2015)
False flax (Camelina sativa L.) is an oil seed crop, a member of Brassicaceae family which has got popularity in biofuel production. The meal of false flax seed has a good potential to be used as a cheap alternative protein source in livestock. False Flax Meal (FFM) has not been used and evaluated in quail diet earlier. The present study was conducted to determine the effects of FFM supplementation in quail diets on growth performance, some carcass characteristics, and lipid oxidation in meat. A total of 300 five-day-old Japanese quails (Coturnix coturnix japonica), including both sexes were divided into 5 groups, each consisting of 60 quails. They were kept in pens and fed a corn-soybean meal-based diet with FFM supplemented at 0% (Control), 5% (FFM5), 10% (FFM10), 15% (FFM15), and 20% (FFM20). The experimental period was lasted for 35 days. Results showed that there were no changes in body weight, body weight gain and feed intake as well as hot and cold carcass weights, relative weight of liver, heart, spleen, gizzard and proventriculus in all experimental groups with FFM supplementation (P>0.05). FCR was impaired in the FFM15 and FFM20 groups compared with the control group (P<0.01). Malondialdehyde levels of serum (P<0.001) and breast meat (P<0.01) decreased in the FFM10, FFM15 and FFM20 groups, whereas serum antioxidant activity level (P<0.01) increased in all experimental groups compared with the control group. In conclusion, it may be stated that dietary supplementation of FFM up to 10% prevents lipid oxidation without any adverse effect on performance and carcass characteristics in quails.
Keywords: False flax meal; performance; carcass; lipid oxidation; quail